1979
DOI: 10.1021/jf60222a049
|View full text |Cite
|
Sign up to set email alerts
|

Role of lipoxygenase and lipid oxidation in quality of oilseeds

Abstract: 1978. The mention of firm names or trade products does not imply that they are endorsed or recommended by the U.S. Department of Agriculture over other firms or similar products not mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Walnuts and pecans are high in unsaturated fatty acids, and therefore can turn rancid by oxidation to free acids from exposure to air (Musco & Cruess, 1954; Maness et al., 1995; Wang et al., 2002). Rancidity of nuts leads to the production of peroxides (Buransompob et al., 2003) and other undesirable compounds that can destroy the nutritive value of the ‘exposed’ nuts (St. Angelo et al., 1979) and therefore can be detrimental for the survival of the feeding larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Walnuts and pecans are high in unsaturated fatty acids, and therefore can turn rancid by oxidation to free acids from exposure to air (Musco & Cruess, 1954; Maness et al., 1995; Wang et al., 2002). Rancidity of nuts leads to the production of peroxides (Buransompob et al., 2003) and other undesirable compounds that can destroy the nutritive value of the ‘exposed’ nuts (St. Angelo et al., 1979) and therefore can be detrimental for the survival of the feeding larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Peanuts are high in oil and fat consisting mainly of unsaturated fatty acid, providing high vulnerability to oxidative rancidity when combined with the high heat treatment of the roasting process ( ). For roasted peanuts, autoxidation is the major cause of oxidative rancidity ( ). Autoxidation in peanuts results in “flavor-fade” and off-flavor development, which may be due to the masking of pyrazines by large amounts of low-molecular-weight aldehydes such as hexanal ( , ).…”
Section: Introductionmentioning
confidence: 99%
“…It remains uncertain whether such oxygen uptake is due to enzymic or nonenzymic oxidations. The remarkable resistance of intact seeds to nonenzymic atmospheric oxidations (24,32) (6,26). The complexities of the interactions with moisture content suggest that there are several mechanisms of seed aging.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the oxidative reactions in the aging process may involve enzymes such as lipoxidase (24,32). Some oxidative enzymes can function at low water activities (1,4,17,20); yet, the possibility of enzyme-induced deterioration of seeds during dry storage has not been widely considered.…”
mentioning
confidence: 99%